Kilali crossing : a tale of despair and desire - Suriyakumaran, Canaganayagam, 1922-2006. (Colombo : Vijitha Yapa Publications, 2002)
Fictionalized account of ethnic tragedy facing to Tamils while crossing kilali water-lane which connected the mainland to the Jaffna Peninsula.
Keywords: Tamil (Indic people) -- Sri Lanka -- Fiction